2016
DOI: 10.1016/j.apme.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Candida Utilis Causing Neonatal Candidemia - A Case Report and Literature Review

Abstract: Candida utilis is rarely described as an agent causing neonatal Candidemia. We report a fatal case of neonatal sepsis caused by C. utilis. Treatment was initiated with fluconazole. Despite resuscitative measures, the infant succumbed on day four of admission in the neonatal intensive care unit. To our knowledge, this is the first case report of C. utilis causing neonatal Candidemia in India. Our report and review highlight the importance of speciation and choice of antifungal therapy for successful clinical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Surprisingly, we isolated emerging Candida species, namely C. dubliniensis , C. fabianii , C. utilis , C. eremophila and C. melibiosica , from infected paediatric patients, which have also been previously isolated in other countries. In agreement with other studies, the majority of these emerging Candida species showed reduced susceptibility to antifungal agents . Uncommon Candida species often go undetected in routine microbiology laboratories, and the clinical significance of these species remains underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we isolated emerging Candida species, namely C. dubliniensis , C. fabianii , C. utilis , C. eremophila and C. melibiosica , from infected paediatric patients, which have also been previously isolated in other countries. In agreement with other studies, the majority of these emerging Candida species showed reduced susceptibility to antifungal agents . Uncommon Candida species often go undetected in routine microbiology laboratories, and the clinical significance of these species remains underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies, the majority of these emerging Candida species showed reduced susceptibility to antifungal agents. 22,[30][31][32][33] Uncommon Candida species often go undetected in routine microbiology laboratories, and the clinical significance of these species remains underestimated. In developing countries, considering the lack of adequate facilities in hospital laboratories, identification of Candida species is limited to conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Candida utilis was the second most common (40.8%) yeast isolated in the present study, contrary to previous reports from our centre where this species was reported at a rate of 0.5%-0.7% from paediatric candidaemia cases. 9,33 There are very few reports of C. utilis candidaemia in literature, 36,37 and the reason for the rise in incidence of C. utilis candidaemia at our centre is unclear. As the majority (95%) of W. anomalus and C. utilis isolates were susceptible to all antifungal agents tested, antifungal drug pressure could not explain their emergence and warrants a systematic epidemiology study.…”
Section: Discussionmentioning
confidence: 94%
“…Only a few studies have reported invasive infection due to C. utilis (reviewed in Table ). Two surveys reported four cases concerning neonates hospitalised in intensive care unit with several risk factors (central venous catheter (CVC), parenteral nutrition, antibiotic therapy and mostly surgical procedure) . One case involved a 68‐year‐old patient suffering from Alzheimer's disease admitted with neurological issues and chronic fever, but with neither neutropoenia nor CVC .…”
Section: Discussionmentioning
confidence: 99%